2018
DOI: 10.1177/0954406218809124
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic analysis of a PPPR spatial serial mechanism with geometric errors

Abstract: The present study focuses on the kinematic analysis of a PPPR spatial serial mechanism with a large number of geometric errors. The study is implemented in three steps: (1) development of a map between the end-effector position error and geometric source errors within the serial mechanism kinematic chains using homogeneous transformation matrix; (2) selection of geometric errors which have significant effects on end-effector positioning accuracy by sensitivity analysis; (3) kinematic analysis of the serial mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…where, bold-italicT P j and bold-italicT R j are the homogeneous matrix of shaft that corresponds to the offset static and the deflection static, respectively. Rot and Trans are rotation and translation operators, 22 respectively. α j is the angle between plane O j x j z j and plane O j x j z j .…”
Section: Analysis Model Of Surface Precisionmentioning
confidence: 99%
See 1 more Smart Citation
“…where, bold-italicT P j and bold-italicT R j are the homogeneous matrix of shaft that corresponds to the offset static and the deflection static, respectively. Rot and Trans are rotation and translation operators, 22 respectively. α j is the angle between plane O j x j z j and plane O j x j z j .…”
Section: Analysis Model Of Surface Precisionmentioning
confidence: 99%
“…In addition, the accuracy analysis solutions for serial, 21,22 single-loop, 23,24 general parallel, 2528 planar multi-loop, 7,29,30 and simple spatial multi-loop mechanisms 20 need to solve the variables directly from constraint equation. However, the support structure is a complex spatial mechanism with multi-loop coupled each other, which belongs to the spatial multi-loop coupled mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Different from the above error sensitivity analysis methods, which were carried out in the global coordinate system, the quantitative interval sensitivity analysis method was presented, and the key geometric errors were identified at different intervals [ 9 ]. Furthermore, for the robot, Feng used a homogeneous transformation matrix to develop the mapping relationship between the end-effector position error and geometric source errors within the serial mechanism kinematic chains, and studied the kinematics of the spatial serial mechanism with a large number of geometric errors [ 10 ]. Li used a full matrix complete differential method to construct the error model of a cable-driven parallel robot, the results confirmed that the cable length errors and pulleys’ geometric errors should be given higher priority in design [ 11 ].…”
Section: Introductionmentioning
confidence: 99%